PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP NILAI PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Perkebunan yang Terdaftar di BEI Periode 2015- 2016) - Debora Ully Natalia Rumajar; Hardi Hardi; Pipin Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The purpose of this research is to examine the effect of Corporate Social Responsibility to Firm Value and Firm Size as a Moderator Variable. The population is all of plantation companies listed in the Indonesia Stock Exchange period 2015-2016. Total sample is 15 companies based on Purposive Sampling methode. Technique of data analysis multiple linear regression analysis using Statistical Product and Service Solution (SPSS) version 25.0 for Windows as data processing software program. The result show that CSR effect on the firm value. It assumes if companies have more of CSR disclosure increase of firm value. In addition, The firm size as a moderating variable showing the result does not effect. Based on the calculation of coefficient determination (R2 ) was 0.128 which is processed using multiple linear regression techniques, CSR with firm value on moderated with firm size simultaneously giving effect was 12.8%. While the remaining 87,2% is influenced by other independent variabel that are not observed in this researchKeywords : corporate social responsibility, firm value, firm size.